2013
DOI: 10.1371/journal.pone.0060409
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Perturbations of Key Metabolites in Diabetic Rats During the Evolution of Diabetes Studied by Urine Metabonomics

Abstract: BackgroundElucidation of metabolic profiles during diabetes progression helps understand the pathogenesis of diabetes mellitus. In this study, urine metabonomics was used to identify time-related metabolic changes that occur during the development of diabetes mellitus and characterize the biochemical process of diabetes on a systemic, metabolic level.Methodology/Principal FindingsUrine samples were collected from diabetic rats and age-matched controls at different time points: 1, 5, 10, and 15 weeks after diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 43 publications
3
48
0
Order By: Relevance
“…Data was visualized using the scores plot of the two principal components (PC1 and PC2), in which each point represented an individual spectrum of a sample. The metabolites associated with the group separations were indicated by the corresponding loading plots, in which each point stood for a metabolite, 16) and were used to identify which metabolite contributed to the separation of the samples on the scores plot. 17,18) The quality of the PLS-DA models was indicated by three parameters (R 2 X, R …”
Section: Gc-ms Determination Of Pq Poisoningmentioning
confidence: 99%
“…Data was visualized using the scores plot of the two principal components (PC1 and PC2), in which each point represented an individual spectrum of a sample. The metabolites associated with the group separations were indicated by the corresponding loading plots, in which each point stood for a metabolite, 16) and were used to identify which metabolite contributed to the separation of the samples on the scores plot. 17,18) The quality of the PLS-DA models was indicated by three parameters (R 2 X, R …”
Section: Gc-ms Determination Of Pq Poisoningmentioning
confidence: 99%
“…Additionally, catabolism of BCAAs can provide intermediates for the TCA cycle, potentially driving energy production (81). The idea that TCA cycle flux is altered in diabetes has been supported in other metabolomics studies in rats and mice (83,84). …”
Section: Metabolomics and Diabetes Researchmentioning
confidence: 80%
“…The detailed acquisition protocol of 1 H-NMR spectra is described in our previous reports [19,22]. All NMR spectra were phase-and baseline-corrected, and then data-reduced to 1100 integrated regions with widths of 0.01 ppm corresponding to the region of ÎŽ10 to -1 using the Topspin 2.1 software package (Bruker Corp., Karlsruhe, Germany) for multivariate pattern recognition analysis.…”
Section: Acquisition Of 1 H-nmr Spectra and Multivariate Pattern Recomentioning
confidence: 99%
“…We previously used this approach and subsequently observed significant changes in energy metabolites, including higher levels of lipids, ketone bodies, and lactate, in the serum of T2DM rats [15,16]. We also have shown that a reduction in energy and the disequilibrium of lipids and methylamine metabolism are closely related to the pathogenic progression of diabetic nephropathy (DN) [17][18][19]. In the present study, we used quantitative and correlative analysis of 1 H NMR spectra of isolated cardiac tissues obtained from diabetic rats to identify the characteristic changes in energy metabolism.…”
Section: Introductionmentioning
confidence: 99%